2017
DOI: 10.1007/s11661-017-4310-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sr Modifier Additions on Double Oxide Film Defects in 2L99 Alloy Castings

Abstract: In this paper, Sr modifier (300 ppm) was added to 2L99 alloy sand castings to investigate its effect on bifilm defects in the castings. Two different sand molds were used in this study, with good and bad running system designs, to introduce different amounts of bifilm defects into the castings. The mechanical properties of the modified 2L99 castings were compared to the properties of unmodified castings and showed that with high bifilm defect contents (H) the Sr addition reduced the Weibull modulus of the UTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The presence of the Ca-containing intermetallic compound particle can be explained by the interfacial segregation of the surface-active Ca and the heterogeneous nucleation of the compound particle on the oxide film. A similar phenomenon was reported by Al-Helal et al [ 86 ] for Al 2 CaSi 2 , as well as by Chen and Griffith [ 87 ] for Al 2 SrSi 2 compound particles.…”
Section: Resultssupporting
confidence: 89%
“…The presence of the Ca-containing intermetallic compound particle can be explained by the interfacial segregation of the surface-active Ca and the heterogeneous nucleation of the compound particle on the oxide film. A similar phenomenon was reported by Al-Helal et al [ 86 ] for Al 2 CaSi 2 , as well as by Chen and Griffith [ 87 ] for Al 2 SrSi 2 compound particles.…”
Section: Resultssupporting
confidence: 89%
“…Nateghian [15] had found that Al 2 O 3 was transformed into SrO when Sr content was as low as 50 ppm and after 5 h of holding, these oxides bond to each other which is known as 'healing' of the bifilms. Chen [16] reported that bifilm quantity and amount of porosity was increased when A356 was modified with Sr.…”
Section: Introductionmentioning
confidence: 99%